2016
DOI: 10.5152/balkanmedj.2015.15742
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of Pregabalin on Cerebral Ischemia and Reperfusion

Abstract: Pregabalin may protect the damage of oxidative stress after ischemia + reperfusion. This result would illuminate clinical studies in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…On the other hand, pretreatment with Pregb and NIL in the hippocampus was found to reverse an elevated NO level to an almost normal control level indicating that these drugs have powerful suppressive oxidant and anti-oxidant defence effects. This action can be further explained on the molecular level by the drug action on NF-κB and NRf2 pathways [7,33]. It was found that Pregb attenuates the expression of p-NF-κB and restore the activity and diminution of phosphorylation of NOS.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, pretreatment with Pregb and NIL in the hippocampus was found to reverse an elevated NO level to an almost normal control level indicating that these drugs have powerful suppressive oxidant and anti-oxidant defence effects. This action can be further explained on the molecular level by the drug action on NF-κB and NRf2 pathways [7,33]. It was found that Pregb attenuates the expression of p-NF-κB and restore the activity and diminution of phosphorylation of NOS.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, PGB showed antianxiety property by attenuation of left amygdala activation during fearful face‐matching and activation of left anterior insula during angry face‐matching, using emotional face‐matching task (Aupperle et al., 2012). The neuroprotection effect of PGB was recently evaluated in reperfusion after cerebral ischemia in rat brain injury (Asci, Demirci, Asci, Doguc, & Onaran, 2016) and also after traumatic brain injury, improving neurological function (Shamsi Meymandi et al., 2018). PGB reduced neuroinflammation, apoptosis, oxidative stress, and fibrosis in the optic nerve of diabetic rats (Ali, Zaitone, Dessouki, & Ali, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Our main results were as follows: 1) the CAT level decreased in Group C, whereas it remained the same in Group P; 2) the TOS decreased in Group P, whereas it increased in Group C; and 3) in Group P, the TAS value in the reperfusion period was higher than that in the ischemia period. Although pregabalin is a GABA analogue, it is a potent new-generation antiepileptic agent; it exerts an effect by binding to the α2δ subunit of voltage-gated calcium channels, which causes a reduction in the Ca ++ influx, and by inhibiting the release of glutamate and noradrenaline from presynaptic terminals [4,8].…”
Section: Discussionmentioning
confidence: 99%
“…Owing to these products, the injury not only causes local tissue damage but also distant organ damage [1]. CAT is one of the most important antioxidant enzymes against ROS [8]. In numerous studies, IMA levels increased in cases of acute ischemia such as that of the skeletal muscles as well as cerebral, myocardial, and pulmonary infarction/ischemia [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation